The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1248/cpb.54.1576
|View full text |Cite
|
Sign up to set email alerts
|

Function of an N-Heterocyclic Carbene Ligand Based on Concept of Chiral Mimetic

Abstract: We have been developing a novel chiral phosphine ligand 1 mimicking axial chirality, in which a chiral carbon center induces a preferred conformation 2a by rotation around an N-Ar bond which is fixed by formation of a chelate structure with metal ( Fig. 1). [1][2][3][4][5][6] In order to expand the scope of our chiral mimetic concept, we planned to develop a novel N-heterocyclic carbene ligand 7-9) 3. The substituent R on the sp 2 N group in the carbene ligand 3 may be conformationally flexible, but if the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…[1][2][3][4][5][6] We have been quite recently developing a novel N-heterocyclic carbene ligand 7,8) 1 based on the concept of chiral mimetic. [7][8][9][10][11][12][13] The N-heterocyclic carbene ligand 1 has been found to construct quaternary carbon streocenters with up to 65% enantioselectivity in Pd-catalyzed enantioselective intramolecular a-arylation of N-(2-bromophenyl)-N-methyl-2-arylpropanamide 2 (Chart 1). The enantioselectivity obtained is, to the best of our knowledge, the high level in the reported literature, 14,15) although the chemical yield is moderate.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] We have been quite recently developing a novel N-heterocyclic carbene ligand 7,8) 1 based on the concept of chiral mimetic. [7][8][9][10][11][12][13] The N-heterocyclic carbene ligand 1 has been found to construct quaternary carbon streocenters with up to 65% enantioselectivity in Pd-catalyzed enantioselective intramolecular a-arylation of N-(2-bromophenyl)-N-methyl-2-arylpropanamide 2 (Chart 1). The enantioselectivity obtained is, to the best of our knowledge, the high level in the reported literature, 14,15) although the chemical yield is moderate.…”
mentioning
confidence: 99%
“…As an application we chose the palladium-catalyzed asymmetric intramolecular a-arylation of amides because chiral oxindole products are of synthetic interest and because the literature precedents for this reaction showed that there was room for improvement in asymmetric induction. [4][5][6] Herein we report the first results of our studies.…”
mentioning
confidence: 88%
“…As an application we chose the palladium-catalyzed asymmetric intramolecular a-arylation of amides because chiral oxindole products are of synthetic interest and because the literature precedents for this reaction showed that there was room for improvement in asymmetric induction.[4-6] Herein we report the first results of our studies.Oxindole alkaloids containing a quaternary benzylic center belong to a large family of natural products that exhibit a variety of significant biological activities, making them interesting and challenging targets for chemical synthesis.[7] Asymmetric transition-metal-catalyzed reactions that provide access to enantiomerically enriched 3-alkyl-3-aryl oxindoles are scarce: Overman and co-workers elegant intramolecular Heck reactions, [8] palladium-catalyzed allylation of 3-arylindoles, [9] and the palladium-catalyzed intramolecular a-arylation of amides, [4][5][6] which are the focus of the present study.Hartwig and Lee tested nineteen mono-and bidentate chiral phosphorous ligands and three in-situ-generated chiral carbene ligands in this reaction, and showed the carbenes outperformed the phosphines.[4] As an example, the best result for the asymmetric cyclization of amide 1 is shown in Scheme 1 together with the results of subsequent reports on this reaction. [5,6] …”
mentioning
confidence: 99%
“…Since then, considerable efforts have been made in this type of reaction [23][24][25][26][27][28][29][30]. However, examples of using chiral N-heterocycliccarbenes in the ligand-catalyzed asymmetric arylation of aldehydes are rare [31][32][33][34][35]. Therefore, developing new chiral N-heterocycliccarbene ligands for the asymmetric 1,2-addition of arylation of aldehydes are rare [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…However, examples of using chiral N-heterocycliccarbenes in the ligand-catalyzed asymmetric arylation of aldehydes are rare [31][32][33][34][35]. Therefore, developing new chiral N-heterocycliccarbene ligands for the asymmetric 1,2-addition of arylation of aldehydes are rare [31][32][33][34][35]. Therefore, developing new chiral N-heterocycliccarbene ligands for the asymmetric 1,2-addition of organoboronic acid to aldehydes is an important synthetic goal.…”
Section: Introductionmentioning
confidence: 99%